Teen Dating Violence in French-speaking Switzerland: Attitudes and Experiences - De Puy, Jacqueline; Hamby, Sherry L.; Lindemuth, Caroline (International Journal of Conflict and Violence (IJCV), 2015)
Research on dating violence has tended to focus on North American college students. This study innovates with data collected in Switzerland from a sample of 132 school pupils and vocational education students aged 14 to 22 using a self-administered questionnaire. The study investigates relationships between attitudes and experiences about dating violence and the effect of gender. Biases against women were common in the sample. Females reported less endorsement of patriarchal attitudes about women’s roles, but both genders reported similar levels of disparagement of women. Participants reported high rates of physical violence perpetration (41.9 percent) and victimization (48.8 percent). Pro-violence attitudes were related to psychological and physical perpetration as well as physical victimization. For female respondents, essentialist beliefs about women’s innate abilities appear more persistent than beliefs about appropriate roles. Male participants endorsed both types of gender stereotypes at high rates. Male-perpetrated violence was perceived less favorably than female-perpetrated violence. Our data suggest that general attitudes toward violence are the most consistent predictor of physical and psychological aggression within dating relationships. More attention needs to be paid to subtypes among attitudes on women and violence, which past research assumed were monolithic. This study shows the need for prevention programs to address pro-violence attitudes.